Preventing the Negative Impact of Gadgets on Psychological Development in Elementary School Children by Implementing Emoji Expression Guidance and Counseling Media - Nilam Suci (Mazidah: Journal Of Educational Research, 2025)
This article was written to complete one of the assignments for the Islamic Education Management course. The method used is library research, namely by collecting data from various literature sources. The purpose of this community service (PkM) is to provide education and counseling to elementary school students (SD) regarding the negative impacts of gadget use on children's psychological development. This PkM activity was carried out at the UPTD SDN 1 Tanjungkerta, Kroya District, Indramayu Regency. This program is a form of intracurricular and implementation of the Tri Dharma of Higher Education. The problem found based on initial observations is that children are accustomed to playing with gadgets beyond the time limit which can cause reduced focus on learning, as well as concerns from teachers and parents because many children use gadgets for negative activities, such as watching pornographic videos. The solution is to provide educational counseling about the negative impacts of gadgets with an illustration of the negative things that can occur, while implementing the Guidance and Counseling (BK) Emoji Expression media as an effort to find out the extent of feelings experienced by children if they do not use gadgets. The methods used in the implementation of the program are lectures, demonstrations, discussions, and questions and answers. The Emoji Expression Guidance and Counseling (BK) media functions as an icon or symbol representing a character and expressing emotions, feelings (moods), and ideas in communication, making it easier for teachers to understand students' conditions. Three forms of expression emerged: happy, sad, and angry. The results of this activity were measured using a pre-test and post-test, analyzed using the N-Gain Test, and showed an improvement between the pre-test and post-test scores for all students. In conclusion, this counseling program ran smoothly and effectively, benefiting teachers by providing engaging and easily understood guidance to students.